SOSIALISASI AKUNTANSI DASAR UNTUK UMKM DI KECAMATAN CIPAYUNG JAKARTA TIMUR - Lidya Primta Surbakti; Dewi Darmastuti; Ekawati Jati Wibawaningsih (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
MSMEs often face financial problems such as poor cash flow, inaccurate recording,. These problems are also experienced by MSMEs in Cipatung District, East Jakarta. Therefore, this Community Service (PkM) activity aims to improve MSMEs' understanding of basic knowledge about accounting that can help them manage their finances better, ensure proper documentation, which ultimately support the stability and growth of their businesses. The method used is to conduct socialization of basic accounting in accordance with the latest standards carried out by Lecturers of the Accounting Department, assisted by the Master of Accounting students, FEB UPN "Veteran" Jakarta using pre-test and post-test instruments and collecting feedback. The impact of this activity is to improve participants’ understanding of basic accounting as evidenced by an increase in the post-test score (score 68.95/100) compared to the pre-test (score 56.8/100). Although the increase in score is not optimal, this score is quite good considering the limited training time and most participants do not have an accounting background. In addition, the feedback result shows that all participants were satisfied and felt that this activity was useful so that participants expressed the need for ongoing training. This activity highlights the importance of strengthening financial literacy for MSME actors to support business sustainability.